Sulfur‐Modified Graphitic Carbon Nitride Nanostructures as an Efficient Electrocatalyst for Water Oxidation. Issue 17 (20th February 2017) - Kale, Vinayak S.; Sim, Uk; Yang, Jiwoong; Jin, Kyoungsuk; Chae, Sue In; Chang, Woo Je; Sinha, Arun Kumar; Ha, Heonjin; Hwang, Chan‐Cuk; An, Junghyun; Hong, Hyo‐Ki; Lee, Zonghoon; et al.
Abstract : There is an urgent need to develop metal‐free, low cost, durable, and highly efficient catalysts for industrially important oxygen evolution reactions. Inspired by natural geodes, unique melamine nanogeodes are successfully synthesized using hydrothermal process. Sulfur‐modified graphitic carbon nitride (S‐modified g‐CN x ) electrocatalysts are obtained by annealing these melamine nanogeodes in situ with sulfur. The sulfur modification in the g‐CN x structure leads to excellent oxygen evolution reaction activity by lowering the overpotential. Compared with the previously reported nonmetallic systems and well‐established metallic catalysts, the S‐modified g‐CN x nanostructures show superior performance, requiring a lower overpotential (290 mV) to achieve a current density of 10 mA cm −2 and a Tafel slope of 120 mV dec −1 with long‐term durability of 91.2% retention for 18 h. These inexpensive, environmentally friendly, and easy‐to‐synthesize catalysts with extraordinary performance will have a high impact in the field of oxygen evolution reaction electrocatalysis. Abstract : An efficient oxygen evolution reaction electrocatalyst with the lowest overpotential in a carbon‐based system comparable to established metal/metal oxide systems (290 mV at 10 mA cm −2, Tafel slope 120 mV dec −1 ) and long‐term durability for 18 h (91.2% retention) is successfully realized from S‐modified graphitic carbon nitride nanostructures. This electrocatalyst is achieved from melamine nanogeodes by in situ sulfur modification at high temperature.